2014
DOI: 10.7287/peerj.preprints.641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nurturing 21st century physician knowledge, skills and attitudes with medical home innovations: the wright center for graduate medical education teaching health center curriculum experience

Abstract: Purpose: Effect of patient centered medical home (PCMH) curriculum interventions on residents’ self-reported and demonstrated knowledge, skills and attitudes (KSA) in PCMH competency arenas is lacking in the literature. This study aimed to assess impact of PCMH curricular innovations on Internal Medicine residents’ self-reported KSA. Method: Twenty four (24) Internal Medicine residents - 12 Traditional (TR) track and 12 Teaching Health Center (THC) track - began training in academic year (AY) 2011 at the Wrigh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Other studies have also shown improvement in knowledge, attitudes, and self-described skills as a result of PCMH training, 13 as well as increased resident response rates to a reminder tool for population management. Initiation of a PCMH curriculum also increased resident satisfaction with care for patients with chronic pain, 15 identified the need for faculty development, 16 and resulted in the development of tools to assess teamwork, 17 efficiency, and quality of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown improvement in knowledge, attitudes, and self-described skills as a result of PCMH training, 13 as well as increased resident response rates to a reminder tool for population management. Initiation of a PCMH curriculum also increased resident satisfaction with care for patients with chronic pain, 15 identified the need for faculty development, 16 and resulted in the development of tools to assess teamwork, 17 efficiency, and quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…11 While concepts of the PCMH have been disseminated for several years, few studies have measured the impact of resident training in the PCMH. [12][13][14][15][16][17][18] Previous PCMH curricular evaluations have shown improvements in knowledge, attitudes, and selfdescribed behaviors. Most studies have not assessed the impact of PCMH training on observed resident behaviors and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%